Płaszcz babiloński we fragmencie 791 Arystofanesa - Rosół, Rafał (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2023)
In the Etymological Dictionary of Akkadian, recently published, the noun pampallu ‘a garment or a woollen cloth’ is accompanied by a short note: “Of interest is a Phrygian word for a ‘coat’ (and the genitals) transmitted by Hesychios: βάμβαλον· ἱμάτιον· καὶ τὸ αἰδοῖον. Φρύγες”. The paper presents some other relevant data, especially Aristophanes’ fragment 791, attested in the lexicon of Photius: βάμβαλον· ἱμάτιον Βαβυλώνιον. οὕτως Ἀριστοφάνης – “bambalon: a Babylonian coat. Aristophanes [says] so”. The final result of the study is that there are two homonyms: 1. βάμβαλον ‘a Babylonian-style warm coat’, and 2. βά(μ)βαλον ‘genitals’. The former is a Semitic borrowing connected with the Akkadian pampallu, the latter is probably Phrygian, but its etymology remains unknown.